A Feasibility Study on the Establishment of Palitwist in #09 Nightingale Zabarte Sub., Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The proponent introduced a high level of information about the business “PaliTwist”. They choose to make a name out of its originality that will be patronized in the market because of its new varieties of flavor. “PaliTwist” was originated from the well-known Filipino delicacy, “Palitaw”, twisting the word, thus, “PaliTwist” came out. We made our Logo into a simple, unique and satisfying one. The Circle shape describe the shape of palitaw and the five circles in the lower part of logo is a representation of the image of the palitaw with their colors and flavors. Said business was located at #09 Nightingale st., Zabarte, Quezon City, with an accessibility to customers and other areas. The researchers conducted a survey inr#09 Nightingale Zabarte Road, Quezon City, We believe that through it we will come to know if the viability and feasibility of the product. The palitwist conducted a survey to know if the product if feasible to the market based on the survey on the respondents answered 98% says Yes they eat palitaw because of the new varieties of flavor and 2% says No because they don’t like kakaninIt indicates that the product is feasible and acceptable in the market. The researchers conducted a survey at the corner of guard house in #09 Nightingale St. Zabarte Road, Quezon City, 90 out of 100 respondents says that the location of the business is reachable. Nowadays, social media is one of the best ways to promote a particular product. The respondents believe that this will be one of the ways which will help promote the product. By implementing and monitoring the company policies will surely reduce high risks and increase the stability of the work force., those employees who make shortcuts to their work and increase the stability on doing thus increasing the sales and profit, The product consistency can be achieved through consistency on production and consistency of the product regarding its size, weight, color and taste. In order to maintain its consistency regarding, the business assures that standard operating procedures are consistently implemented.
Keywords: palitwist, viability, feasible, consistency, quantity